Efektivitas Pencegahan Gangguan Keamanan dan Ketertiban melalui Sarana Hukum (Studi Kasus Rutan Kelas IIA Palangka Raya): Penelitian - Miftakhul Anam; Bahtiyar Mandala Sutra; Ramiyanto (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to analyze various forms of security and order disturbances at the Palangka Raya Class IIA Detention Center and identify the legal means used to prevent such disturbances. The method used is empirical legal research with a qualitative approach. Data collection techniques include interviews, observations, and literature reviews, with sources such as the prison warden, head of security, security officers, as well as inmates and prisoners. The results of the study show that security and order disturbances still occur in physical forms such as fights and escape attempts, as well as non-physical forms such as drug trafficking and violations of regulations. Prevention efforts through legal means, such as routine raids, personality development, and early detection, have been implemented with fairly effective results, although not yet optimal. Major challenges include a shortage of staff, inadequate surveillance facilities, and weak inter-agency coordination. However, supportive factors such as leadership commitment, staff training, and the active role of the early detection team contribute to maintaining security stability within the detention center. This study is expected to contribute to the formulation of more effective and preventive correctional policies.